Study of the effect of government on the innovation performance of private sector enterprises - Cory, Katherine J. (2010)
This study looks at the key research in innovation performance of private enterprises and how this is affected by the government. This focuses on university knowledge transfer and public procurement as a facilitator of private sector innovation. The study will review the relevant academic literature and statistical graphs produced by certain research bodies before going on to analyse UK enterprise preferences through multiple regression analysis of the UK Community Innovation Survey 4. Finally, conclusions based on this analysis, including overviews of unexpected effects are extracted before finally finishing with conclusions and suggestions for future research.